Climate Change Impacts on Agricultural Water Stress and Impact Mitigation Potential - Gerten, Dieter; Rost, Stefanie (Washington, DC: World Bank, 2012)
Food production is strongly water-limited in many regions, reflecting the fact that under dry conditions the amount of water in the soil is not sufficient to sustain optimal plant growth. This paper provides a geographically explicit quantification of a) the current (1971-2000 average) blue and green water consumption in global agriculture; b) the current and possible future (2041-2070 average) water limitations to crop production; and c) the potential to mitigate this limitation through rainwater harvesting and vapor shift management strategies.